THE EFFECT OF USING JIGSAW STRATEGY ON IMPROVING THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 12 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Lilis Litawati; Fadly Azhar; Afrianto Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This experimental study is aimed at finding out whether the use of jigsaw strategy is effective to improve students’ reading comprehension. This research was conducted at SMAN 12 Pekanbaru from September 27, 2017 to November 01, 2017. Cluster Sampling technique was used to choose 40 students as the participants. Data used in this research were the data about students’ reading comprehension. Therefore, Reading Comprehension Test was used as the instrument. Then, the data were analyzed by using SPSS 23.0 for windows. The result of the research showed that there was a significant effect of jigsaw strategy on the students’ reading comprehension. The mean score of the students before the treatment was 61.87, While the mean score of the students after the treatment was 80.77. Moreover, from the statistical analysis, it was found that the t-test score (22.5) was higher than t-table (2.03). Based on these findings, it is suggested that Jigsaw strategy can be used as an alternative strategy in the teaching of reading.Keywords: Jigsaw Strategy, Descriptive Text, Experimental Research